Faktor Risiko Kejadian Pre-Eklampsia di RSUD Arifin Achmad - Rika Andriyani (STIKes Hang Tuah Pekanbaru, 2012)
Indonesia's maternal mortality rate is still high. Causes of maternal mortality in Indonesia namely hemorrhage (6070%), eclampsia (10-20%), obstructed labor (5%) and infections (8%). Pre-eclampsia is the onset of eclampsia. Preeclampsia is a disease with signs of hypertension, edema, and proteinuria caused by pregnancy pre-eclampsia can occur due to multiple risk factors such as primigravida, large fetus, pregnancy with a single fetus. This study aimed to determine the factors associated with the incidence of pre-eclampsia at Arifin Achmad Hospital Riau Province Year 2010-2011. Case study research design is control. Cases in this study all women who developed pre-eclampsia in the year 2010-2011. Controls in this study all women who did not develop pre-eclampsia in the year 2010-2011. The result showed that mothers with a history of pre-eclampsia 5 times (95% CI 2.3-10.8) greater risk of pre-eclampsia causes, working mothers 3.5 times (95% CI 2.4-5.2) greater risk of pre-eclampsia causes, maternal age <20 or> 35 years 3.2 times (95% CI 2.2-4.8) greater risk of pre-eclampsia has occurred, Mrs. primigravida 3.2 times (95% CI 2.1-4.7) greater risk of pre-eclampsia leads to mother junior secondary education 2.3 times (95% CI 1.6-3.3) greater risk of pre-eclampsia causes compared with high school education or more. The conclusion that the independent variables that have a causal relationship with the incidence of pre-eclampsia is a history of pre-eclampsia, occupation, age, gravida status and education. Suggestions intended for health professionals to perform a comprehensive examination, the assessment and physical examination, and for the mother to be able to conduct an intensive examination of the ANC, as well as increasing the frequency of examinations during pregnancy